ANALISIS STRATEGI EKONOMI KREATIF DENGAN METODE TRIPLE HELIX PADA UMKM PAYUNG GEULIS DI KOTA TASIKMALAYA - Mardiana, Rosa; Rosmawati, Servia; Sartika, Sri Hardianti (Transpublika Publisher, 2022)
Payung geulis is one of the icons of the creative economy of the city of Tasikmalaya which has its own characteristics in its manufacture. This study aims to analyze the creative economy development strategy at Payung Geulis SMEs in the city of Tasikmalaya and the strategy used in this creative economy development is a SWOT analysis strategy with the Triple Helix method. In this study, data collection in the form of qualitative methods was also carried out by conducting observations and interviews at one of the Payung Geulis businesses in Tasikmalaya. The results of this study indicate that the Payung Geulis by Nailah Collection has decreased in production with a lack of promotional strategies, it will have an impact on the sustainability of the ongoing business. Based on the SWOT analysis that has been carried out, it can help business actors to be able to determine the strategies that must be carried out first in order to achieve the desired goals. Based on this decrease, it is necessary to have creativity and innovation in various ways in order to increase the production of this Payung Geulis business. Hence, it can be concluded that the creative economy strategy with the Triple Helix method in this Payung Geulis business can be said to be relatively dependent on the promotion strategy carried out by business actors.